HLA-G Expressing Immune Cells in Immune Mediated Diseases - Contini, P.; Murdaca, Giuseppe; Puppo, Francesco; Negrini, Simone (Frontiers in Immunology, 2020)
HLA-G is a HLA class Ib antigen that possesses immunomodulatory properties. HLA-G+CD4+, HLA-G+CD8+ and HLA-G+CD4+ regulatory T cells with immune-suppressive and immunoregulatory functions are present in small amounts in physiologic conditions. Increased amounts of these HLA-G positive cells have been detected in several immune mediated diseases, like multiple sclerosis, psoriasis, systemic lupus erythematosus and systemic sclerosis. Further investigations are required in order to define a possible role of HLA-G positive immune cells in the pathogenesis of immune mediated diseases.